2000
DOI: 10.1161/01.atv.20.12.2689
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Induction of a Releasable Pool of Factor VIII in Human Endothelial Cells

Abstract: Abstract-Although it is known that factor VIII (FVIII) plasma levels increase rapidly in response to a number of stimuli, the biological stimuli behind this release is less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 43 publications
2
59
0
2
Order By: Relevance
“…3 Moreover, transplantation of LSEC offers therapeutic potential in coagulation disorders, including hemophilia A. 18,47 Besides the possibility of transducing cultured LSEC via retroviral and lentiviral vectors, 48,49 the feasibility of lentiviral gene transfer in freshly isolated LSEC, as shown here, will offer additional opportunities for cell and gene therapy.…”
Section: Discussionmentioning
confidence: 92%
“…3 Moreover, transplantation of LSEC offers therapeutic potential in coagulation disorders, including hemophilia A. 18,47 Besides the possibility of transducing cultured LSEC via retroviral and lentiviral vectors, 48,49 the feasibility of lentiviral gene transfer in freshly isolated LSEC, as shown here, will offer additional opportunities for cell and gene therapy.…”
Section: Discussionmentioning
confidence: 92%
“…3,21 Transfected AtT-20 cells were grown on 35-mm culture plates (Fisher Scientific, Itasca, IL) in Dulbecco modified Eagle medium/G418 media for 72 hours. Negative controls (nontransfected and mock-transfected cells) were processed in parallel with each immunofluorescence labeling experiment.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Recent studies have suggested that it may be beneficial to express FVIII in cells that also express its natural carrier protein von Willebrand factor (VWF). [5][6][7][8][9][10][11] In the circulation, VWF protects FVIII from premature clearance and proteolytic degradation by virtue of its ability to bind to it with high affinity. [12][13][14] VWF is expressed in megakaryocytes and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Expression of FVIII in endothelial cells results in storage of FVIII in WPBs. 6,19,20 Co-storage of the VWF/FVIII complex in secretory granules and subsequent release of the VWF/FVIII complex upon agonist-induced stimulation has the potential of secreting large amounts of FVIII at sites of vascular injury as well as directly increasing FVIII half-life by protecting FVIII from premature clearance and proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%